2013
DOI: 10.1158/1078-0432.ccr-12-1956
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Food and Drug Administration Approval: Vismodegib for Recurrent, Locally Advanced, or Metastatic Basal Cell Carcinoma

Abstract: The data and regulatory considerations leading to the U.S. Food and Drug Administration (FDA) January 30, 2012 approval of Erivedge (vismodegib) capsules for the treatment of patients with recurrent, locally advanced, or metastatic basal cell carcinoma (BCC) are described. The FDA's approval decision was based primarily on the results observed in a single-arm, parallel cohort, international trial of vismodegib, administered orally at 150 mg daily until disease progression, in patients with pathologically confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 21 publications
2
111
1
1
Order By: Relevance
“…They found that IL-23 signaling promotes tumor growth and progression, and the development of tumoral IL-17 response, resulting in an additional aggravation of disease progression (60). Efforts to target pathogenic Hedgehog signaling have steadily progressed from the laboratory to the clinic, and the recent approval of vismodegib for patients with advanced basal cell carcinoma represents an important milestone (61)(62)(63)(64)(65)(66). However, in a recent phase II study, vismodegib did not add to the efficacy of standard first-line treatment for metastatic colorectal cancer (67).…”
Section: Discussionmentioning
confidence: 99%
“…They found that IL-23 signaling promotes tumor growth and progression, and the development of tumoral IL-17 response, resulting in an additional aggravation of disease progression (60). Efforts to target pathogenic Hedgehog signaling have steadily progressed from the laboratory to the clinic, and the recent approval of vismodegib for patients with advanced basal cell carcinoma represents an important milestone (61)(62)(63)(64)(65)(66). However, in a recent phase II study, vismodegib did not add to the efficacy of standard first-line treatment for metastatic colorectal cancer (67).…”
Section: Discussionmentioning
confidence: 99%
“…As detailed knowledge regarding the molecular pathogenesis of BCC has been elucidated, multiple targeted therapies have been developed to target aberrant HH signaling. Vismodegib, a small molecule agent that binds to and directly inhibits SMO was recently FDA approved for recurrent, locally advanced, or metastatic basal cell carcinoma [32]. Targeted therapy has also been attempted in NBCCS; for example, a phase II study examining the efficacy of vismodegib in NBCCS found a significant reduction in surgically eligible BCCs encountered in the treatment group (2 per patient) versus the control group (29 per patient).…”
Section: Screening and Treatmentmentioning
confidence: 99%
“…The smoothened inhibitor vismodegib has recently been approved for treating BCC in patients with NBCCS [74]. Unfortunately, 20% of all treated tumors developed resistance within one year of treatment; and mutations in SUFU have been proposed as a mediator of this resistance mechanism [75].…”
Section: Treatment Success and Limitationsmentioning
confidence: 99%